Keterlibatan Uni Eropa Dalam Mengatasi Perompakan di Somalia Tahun 2008-2015 - Tobing, Gracia Gerina L; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Somalia is a state located at the Horn of Africa which is geographically strategic. Somalia Sea to the Gulf of Aden is an essential route used by foreign ships as international trade route. The emergence of Somali Piracy cases in international seas has become quite a threat for several years. Piracy has harmed European Union states and brought negative effect towards the global trade route. European Union, an international institution which concerns on global issue, made cooperation with Somalia. The purpose of this research was to know the motive behind European Union’s involvement in Somalia. This research used explanative method with institutional liberalism perspective and collective security concept to explain this matter. The result of this research shows the involvement of the EU in Somalia departs from its fundamental principles where foreign policy takes four main forms which are Enlargement, Stabilization, Bilateralism and Interregionalism. This approach is based on active diplomacy, support for political change, increased security, development assistance and humanitarian assistance. A comprehensive approach in the Somali piracy case is determined by the fact that military missions in Somali waters are only a short-term solution and improvements in programs must be increased in order to get the expected impact. EU hopes to guarantee security on an ongoing basis by establishing maritime ship surveillance operations and maritime training on land. EU recognizes the interdependence of various global security challenges by linking security issues and highlighting the possibility of interaction between piracy threats.